Deletion of Gli3 in mice causes abnormal frontal bone morphology and premature synostosis of the interfrontal suture - Veistinen, Lotta; Takatalo, Maarit; Kesper, Dörthe A.; Vortkamp, Andrea; Rice, David P. (Frontiers in Physiology, 2012)
Greig cephalopolysyndactyly syndrome (GCPS) is an autosomal dominant disorder with polydactyly and syndactyly of the limbs and a broad spectrum of craniofacial abnormalities. Craniosynostosis of the metopic suture (interfrontal suture in mice) is an important, rare feature associated with GCPS. GCPS is caused by mutations in the transcription factor GLI3, which regulates Hedgehog signaling. The Gli3 null allele (Gli3Xt-J/Xt-J) mouse largely phenocopies the human syndrome with the mice exhibiting polydactyly and several craniofacial abnormalities. Here we show that Gli3Xt-J/Xt-J mice exhibit ectopic ossification in the interfrontal suture and in the most severe cases the suture fuses already prior to birth. We show that abnormalities in frontal bones occur early in calvarial development, before the establishment of the interfrontal suture. Thus in this aspect the Gli3Xt-J/Xt-J mouse mimics GCPS patients with GLI3 mutations and metopic suture abnormalities. It provides a model for the metopic suture pathology that can occur in GCPS.